2018
DOI: 10.1002/term.2665
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation of freshly isolated human adipose tissue-derived stromal vascular fraction cells by pulsed light-emitting diodes for direct clinical application

Abstract: A highly interesting source for adult stem cells is adipose tissue, from which the stromal vascular fraction (SVF)-a heterogeneous cell population including the adipose-derived stromal/stem cells-can be obtained. To enhance the regenerative potential of freshly isolated SVF cells, low-level light therapy (LLLT) was used. The effects of pulsed blue (475 nm), green (516 nm), and red (635 nm) light from light-emitting diodes applied on freshly isolated SVF were analysed regarding cell phenotype, cell number, viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…8b). These results indicated the excellent adipogenic differentiation potential of the microtissue-SVF, as adipogenic differentiation is detected after 14-21 d of induction in previous studies (Priglinger et al, 2018;Priglinger et al, 2017). Upon osteogenic induction, expression of the specific osteogenic markers ALPL, BGLAP and SPP1 was increased after 21 d, being significant for BGLAP and SPP1 (Fig.…”
Section: The Microtissue-svf Was Successfully Integrated Into the Sursupporting
confidence: 80%
See 1 more Smart Citation
“…8b). These results indicated the excellent adipogenic differentiation potential of the microtissue-SVF, as adipogenic differentiation is detected after 14-21 d of induction in previous studies (Priglinger et al, 2018;Priglinger et al, 2017). Upon osteogenic induction, expression of the specific osteogenic markers ALPL, BGLAP and SPP1 was increased after 21 d, being significant for BGLAP and SPP1 (Fig.…”
Section: The Microtissue-svf Was Successfully Integrated Into the Sursupporting
confidence: 80%
“…For a potential cell therapeutic, it is important to deliver highly regenerative cell types (Corselli et al, 2013), which were found in the microtissue-SVF by subpopulation screening. Distinct regenerative SVF populations, such as Muse cells [a stress resistant stem cell population (Kuroda and Dezawa, 2014)], a pericytic subset CD90 + /CD146 + (Priglinger et al, 2017) and lymphatic endothelial cells, were present in the microtissue-SVF. Kuroda et al (2010) show that Muse cells can be obtained as a minor subset from MSCs and are able to differentiate into ectodermal, endodermal and mesodermal lineage in vivo and have the capacity to replace damaged tissue, as demonstrated for liver regeneration (Katagiri et al, 2016).…”
Section: Fig 4 Flow Cytometry Analysis Of Svf Subpopulationsmentioning
confidence: 99%
“…Zhang, Xiong et al, (2009) also demonstrated that red LED irradiation (650 nm) attenuated the elevation of VEGF expression in HeLa cell implanted BALB/c mice. However, data from Priglinger et al, (2018) using the red LED irradiation, although with different parameters than that used in the present work, demonstrated its beneficial effects on the vascularization potential of stromal vascular fraction (SVF), the heterogeneous cell population including the ASC.…”
Section: Discussionmentioning
confidence: 69%
“…A second Scopus database search was undertaken to evaluate the effects of green light PBM using the terms described in Figure 3b. An initial search resulted in 236 articles being identified and these articles were subsequently screened for suitability, which then identified 32 relevant articles for further review (18,32,33,64,68,69,79,164,168,171,176,177,186,197,205,209,(212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225)(226)(227).…”
Section: Kazemi Khoo Et Al 2013(184)mentioning
confidence: 99%